2020
DOI: 10.1371/journal.pone.0236985
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the facility: An evaluation of seven community-based pediatric HIV testing strategies and linkage to care outcomes in a high prevalence, resource-limited setting

Abstract: Diverse challenges in expanding pediatric HIV testing and treatment coverage persist, making the investigation and adoption of innovative strategies urgent. Evidence is mounting for the effectiveness of community-based testing in bringing such lifesaving services to those in need, particularly in resource-limited settings. The Mobilizing HIV Identification and Treatment project piloted seven community-based testing strategies to assess their effectiveness in reaching HIV-positive children and linking them to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Several studies noted phone-or home-based tracing by community health workers for all newly diagnosed clients [11] or for clients that were not linked to HIV services [13,[17][18]. The PoP-ART-Y study found high linkage rates in young adolescents 10-14 years (92.9% in boys, 98.2% in girls) with multiple active linkage interventions including escorts to clinics, specially-trained counselors, use of community health workers to track clients, and multi-disciplinary meetings to review those not yet linked to care or initiated on ART [19]. Another study from Kenya showed improved linkage rates in 10-14-year-old children after an adolescent-focused intervention that included capacity building, extended clinic hours, and program tools (53.8% to 83.6% for boys, 44.8% to 94.7% for girls) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies noted phone-or home-based tracing by community health workers for all newly diagnosed clients [11] or for clients that were not linked to HIV services [13,[17][18]. The PoP-ART-Y study found high linkage rates in young adolescents 10-14 years (92.9% in boys, 98.2% in girls) with multiple active linkage interventions including escorts to clinics, specially-trained counselors, use of community health workers to track clients, and multi-disciplinary meetings to review those not yet linked to care or initiated on ART [19]. Another study from Kenya showed improved linkage rates in 10-14-year-old children after an adolescent-focused intervention that included capacity building, extended clinic hours, and program tools (53.8% to 83.6% for boys, 44.8% to 94.7% for girls) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Reported linkage rates of enrollment into HIV services or ART initiation rates in CLHIV vary widely across studies (45–100%) [ 9 – 18 ], likely due to differing time points for follow-up assessments, different settings of HIV testing and diagnosis, and different age bands. For instance, one study from Cameroon found that linkage rates to HIV care or ART initiation were higher in index testing strategies compared to outpatient department (OPD) (85.0% vs. 52.5%) and in children ≤12 years compared to children 13–19 years [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, including ours, did not capture or report details around strategies for supporting linkage. Several studies noted phone- or home-based tracing by community health workers for all newly diagnosed clients [ 11 ] or for clients that were not linked to HIV services [ 13 , 17 , 18 ]. The PoP-ART-Y study found high linkage rates in young adolescents 10–14 years (92.9% in boys, 98.2% in girls) with multiple active linkage interventions including escorts to clinics, specially-trained counselors, use of community health workers to track clients, and multi-disciplinary meetings to review those not yet linked to care or initiated on ART [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations